Take the next step leading lasting change in the church - Weems, Lovett H. (Lovett Hayes) (Nashville : Abingdon Press, 2003)
Learn how to work for genuine and effective change in your church without trying to throw out everything that has gone before.
Includes bibliographical references (p. 160-166) and index.
Print version record.
Keywords: Christian leadership; RELIGION / Christian Ministry / Pastoral Resources; Electronic books